2021
DOI: 10.3390/md19040219
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SARS-CoV-2 Virus Entry by the Crude Polysaccharides of Seaweeds and Abalone Viscera In Vitro

Abstract: Much attention is being devoted to the potential of marine sulfated polysaccharides as antiviral agents in preventing COVID-19. In this study, sulfated fucoidan and crude polysaccharides, extracted from six seaweed species (Undaria pinnatifida sporophyll, Laminaria japonica, Hizikia fusiforme, Sargassum horneri, Codium fragile, Porphyra tenera) and Haliotis discus hannai (abalone viscera), were screened for their inhibitory activity against SARS-CoV-2 virus entry. Most of them showed significant antiviral acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 30 publications
0
47
0
Order By: Relevance
“…Recently, sulfated polysaccharides have earned significant attention for their effective inhibitory effects against SARS-CoV-2 ( Hans et al, 2020 ; Kwon et al, 2020 ), such as heparin ( Ayerbe et al, 2020 ), fucoidan ( Song et al, 2020 ), and carrageenan ( Jang et al, 2021 ). These sulfated polysaccharides could bind to the SARS-CoV-2 spike glycoprotein, so to prevent virus entry into the host cells ( Yim et al, 2021 ). Given that the COVID-19 epidemic is still going on, more efforts are needed to discover effective anti-virus agents against SARS-CoV-2 in the present urgent situation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, sulfated polysaccharides have earned significant attention for their effective inhibitory effects against SARS-CoV-2 ( Hans et al, 2020 ; Kwon et al, 2020 ), such as heparin ( Ayerbe et al, 2020 ), fucoidan ( Song et al, 2020 ), and carrageenan ( Jang et al, 2021 ). These sulfated polysaccharides could bind to the SARS-CoV-2 spike glycoprotein, so to prevent virus entry into the host cells ( Yim et al, 2021 ). Given that the COVID-19 epidemic is still going on, more efforts are needed to discover effective anti-virus agents against SARS-CoV-2 in the present urgent situation.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that SX effectively interferes with interaction of S-glycoprotein and ACE2, but FX does not. In recent studies, sulfated polysaccharides [ 28 , 29 ], fucoidan [ 30 ], and some crude polysaccharide extractions [ 31 ] effectively inhibited SARS-CoV-2 entry in vitro. According to studies so far, highly branched and sulfated polysaccharides with high molecular weight can effectively inhibit COVID-19 viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Besides inhibiting viral attachment, algal-derived sulfated glycans also inhibit virus penetration, exteriorization, uncoating, transcription, and translation processes [27]. Indeed, in previous work, the fucoidan from brown alga and the carrageenan from red alga possess antiviral activity [26,[28][29][30]. In this research, we found that RS from M. nitidum is as competitive as the fucoidans and iota-carrageenan in its potential to combat COVID-19 [26,28], which is reflected by its high capacity in binding the S-protein and neutralizing the pseudotyped virus in vitro.…”
Section: In Vitro Sars-cov-2 Pseudotyped Virus Neutralizationmentioning
confidence: 98%